Sport Development Index Analysis of Sukoharjo Regency - Latif, Annas Abdul; Rahayu, Setya; Raharjo, Hermawan Pamot (Journal of Physical Education and Sports, 2023)
The sports development index is a way to measure the progress of sports development through four indicators, namely: open space, human resources, community participation and physical fitness. The aim of the research is to analyze sports development in Sukoharjo Regency using these indicators. This research took 3 sub-district samples, namely Sukoharjo sub-district, Grogol sub-district and Mojolaban sub-district including quantitative analysis research. The sampling technique is cluster sampling. The tools used are observation, questionnaires, interviews and multistage fitness tests to examine public health data. The results of research in Sukoharjo Regency are (1) the open space index value is 0.355l (2) the sports human resources index is 0.00057, (3) the community participation index result is 0.455 (4) the fitness index value is 0.363. The overall sports development index (SDI) value of Sukoharjo Regency is 0.245. The conclusion of this research is that the SDI index of Sukoharjo Regency is still low because the total SDI index covering open space, human resources, sports participation and fitness of Sukoharjo Regency residents is 0.245 which is always between the values 0-0.499. This means that sports development in Sukoharjo Regency is still far from progressing, there are many things that need to be considered and resolved by the district government to advance sports in Sukoharjo Regency.